Research progress in Traditional Chinese Medicine nursing of chronic atrophic gastritis (慢性萎缩性胃炎中医护理研究进展) - LIU Fenghua (刘凤华); ZHANG Xianyao (张先姚) (中西医结合护理)
Chronic atrophic gastritis (CAG) is a common digestive system disease and a type of chronic gastritis disease progression. The study found that its incidence rate and detection rate increased significantly with age. Currently, there is no definitive treatment in Western medicine, and conservative treatment in traditional Chinese medicine is mostly used in clinical practice. This method can delay or prevent the progression of the disease, reduce the risk of cancer, and improve the clinical symptoms of patients. This article mainly reviews the commonly used Traditional Chinese medicine nursing methods for patients with chronic atrophic gastritis in recent years, and provided reference for establishing strategies for clinical nursing practice. (慢性萎缩性胃炎(CAG)是临床常见的消化系统疾病, 是慢性胃炎疾病进展的一种类型, 随年龄的增长其发病率及检出率明显增加。目前临床治疗CAG以保守治疗为主, 延缓或阻止病变的进展、降低癌变风险, 改善患者的临床症状。本研究就CAG临床常用的中医护理方法进行综述, 以期为CAG患者护理策略的制定提供有效参考。)